Entrepreneurial Orientation and International Fundraising by Civil Society Organizations - Mariana Cristina Betti Cury Lorca (FUCAPE Business School, 2020)
This article examines how certain Civil Society Organizations (CSOs) from Emerging Economies (EE) are able to raise funds from International Development Agencies (IDAs) while others are not successful in this endeavor. Following a multiple case study involving six Brazilian CSOs, our results suggest that one of the factors that explain the success of CSOs in international fundraising is Entrepreneurial Orientation (EO), which allows some of them to develop innovative approaches aligned with the guidelines of international development agencies. These results contribute to the expansion of the theoretical domain in which the EO construct is important for international fundraising, a field that has been explored little in the literature. From a practical viewpoint, the study suggests that CSOs that wish to raise funds from IDAs should promote EO internally.